CORTICOSTEROIDS AND MENTAL HEALTH: NEUROPSYCHIATRIC CONSEQUENCES - Peixoto dos Santos, Bruno; Peixoto dos Santos, Isabella (Revista Pulmão, 2025)
INTRODUCTION: Corticosteroids, essential steroid hormones synthesized mainly in the adrenal cortex, play critical roles in regulating metabolism, immune responses, and overall physiological functions, featuring a molecular structure that facilitates their interaction with cell membranes and cellular functions. The secretion of corticosteroids like cortisol follows a diurnal and ultradian rhythm, regulated by the hypothalamicpituitary-adrenal (HPA) axis, ensuring daily physiological homeostasis and a rapid response to stress via increased production triggered by ACTH and various stressors. While corticosteroids are invaluable in treating inflammatory and autoimmune conditions due to their anti-inflammatory and immunosuppressive properties, their therapeutic use requires careful management to balance beneficial effects against potential adverse outcomes, including metabolic disturbances, mood changes, and increased infection risk. OBJETIVE: Analyze and describe the main aspects of the neurological and psychiatric repercussions of chronic exposure to corticosteroids in the last years. METHODS: Studies in the MEDLINE – PubMed (National Library of Medicine, National Institutes of Health), COCHRANE, EMBASE and Google Scholar databases. RESULTS AND DISCUSSION: Longterm corticosteroid therapy is crucial for managing various chronic conditions but is associated with significant psychological and psychiatric effects that adversely affect patient quality of life, including mood disturbances, anxiety, and cognitive impairments. These effects are influenced by factors such as dosage, duration of therapy, and individual characteristics like age and pre-existing mental health conditions, necessitating tailored management strategies that integrate pharmacological treatments, psychotherapy, and lifestyle modifications. The complexity of these side effects demands vigilant monitoring and comprehensive care approaches, underscored by a need for ongoing research to explore the neurobiological mechanisms involved and to develop effective interventions tailored to the diverse needs of patients across different chronic conditions. CONCLUSION: Long-term corticosteroid therapy significantly impacts psychological and psychiatric health, necessitating comprehensive management strategies that include pharmacological, psychotherapeutic, and lifestyle interventions tailored to individual patient needs. Factors such as dosage, therapy duration, underlying disease, and individual characteristics like age and mental health history influence the severity of these effects, highlighting the need for personalized treatment plans and regular mental health monitoring. There is a critical need for further research, including longitudinal studies and randomized controlled trials, to better understand the psychiatric effects of corticosteroids and to develop more effective intervention strategies.